Quadratic Recurrence

Algebra Level 4

{ a n } \{ a_n \} is a sequence such that a 1 = 4 3 a_1=\dfrac{4}{3} , a n + 1 = a n 2 a n + 1 a_{n+1}=a_n^2-a_n+1 , the recurrence holds for integer n 2 n \geq 2 .

For every positive integer n 1 n \geq 1 , what is the set of all possible values of i = 1 n 1 a i \left \lfloor \displaystyle \sum_{i=1}^n \dfrac{1}{a_i} \right \rfloor ?

Warning: This sequence is proved to have no closed form . Don't waste your time trying to find the formula of { a n } \{ a_n \} .

{ 0 , 1 , 2 , 3 } \{0,1,2,3\} { 0 , 2 } \{0,2\} { 0 , 1 , 2 } \{0,1,2\} { 1 , 2 } \{1,2\}

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Aug 26, 2019

Define S n = j = 1 n x j 1 S_n \; = \; \sum_{j=1}^n x_j^{-1} It is easy to calculate that S 1 = 0 \lfloor S_1\rfloor = 0 , S 2 = 1 \lfloor S_2 \rfloor = 1 and S 3 = 2 \lfloor S_3 \rfloor =2 .

It is also a simple induction to show that x n > 1 x_n > 1 for all n 1 n \ge 1 , and therefore that x n + 1 x n = ( x n 1 ) 2 > 0 x_{n+1}-x_n = (x_n-1)^2 > 0 for all n 1 n \ge 1 , so that the sequence x n x_n is increasing. Now note that 1 x n 1 1 x n + 1 1 = x n + 1 x n ( x n 1 ) ( x n + 1 1 ) = ( x n 1 ) 2 ( x n 1 ) x n ( x n 1 ) = 1 x n \frac{1}{x_n-1} - \frac{1}{x_{n+1}-1} \; = \; \frac{x_{n+1}-x_n}{(x_n-1)(x_{n+1}-1)} \; = \; \frac{(x_n-1)^2}{(x_n-1)x_n(x_n-1)} \; = \; \frac{1}{x_n} for all n 1 n \ge 1 , so that S n = j = 1 n x j 1 = j = 1 n ( 1 x j 1 1 x j + 1 1 ) = 1 x 1 1 1 x n + 1 1 = 3 1 x n + 1 1 < 3 S_n \; = \; \sum_{j=1}^n x_j^{-1} \; = \; \sum_{j=1}^n \left(\frac{1}{x_j-1} - \frac{1}{x_{j+1}-1}\right) \; = \; \frac{1}{x_1-1} - \frac{1}{x_{n+1}-1} \; = \; 3 - \frac{1}{x_{n+1}-1} \; < \; 3 for all n 1 n \ge 1 . Thus ( S n ) n (S_n)_n is an increasing sequence that is bounded above, and so it converges. Hence x n 1 0 x_n^{-1}\to0 as n n \to \infty , so that x n x_n \to \infty as n n \to \infty . But this implies that S n 3 S_n \to 3 as n n \to \infty . Since S n < 3 S_n < 3 for all n 1 n\ge 1 , with lim n S n = 3 \lim_{n \to\infty}S_n = 3 , we deduce that the correct answer is { 0 , 1 , 2 } \boxed{\{0,1,2\}} .

As simple calculations show, the sequence ( x n ) n (x_n)_n diverges to \infty extremely rapidly!

But n n is claimed to be 2 ≥2 . So the answer must be { 1 , 2 1,2 }.

Alapan Das - 1 year, 9 months ago

Log in to reply

No, the recurrence relation is only defined for n 2 n \ge 2 , because it is linking x n x_n and x n 1 x_{n-1} (and x 0 x_0 does not exist), but x n x_n exists for all n 1 n \ge 1 . Thus S n S_n exists for all n g e 1 n\ ge 1 .

Mark Hennings - 1 year, 9 months ago

But that should be clearly explained. Many other like me can think it wrong.

Alapan Das - 1 year, 9 months ago

Log in to reply

It seems that the question has been clarified. However, according to the way you read the problem, if I define the Fibonacci numbers by the recurrence relation F 0 = 0 F 1 = 1 F n = F n 1 + F n 2 ( n 2 ) F_0 = 0 \hspace{0.5cm} F_1 = 1 \hspace{1cm} F_n \; = \; F_{n-1} + F_{n-2} \;\;\;(n \ge 2) and then talk later about the sequence of Fibonacci numbers ( F n ) n (F_n)_n , you would argue that I am no longer talking about F 0 F_0 and F 1 F_1 , which is clearly wrong. In the definition, the condition n 2 n\ge2 defines the range of validity of the dummy variable n n in the recurrence relation, and does not define the domain of F F , since the full definition (recurrence relation plus initial conditions) defines F n F_n for all n 0 n \ge 0 .

Mark Hennings - 1 year, 9 months ago

What was your motivation behind this beautiful solution, Sir?

Basu Bhowmick - 1 year, 7 months ago
Zk Lin
Aug 29, 2019

From a n + 1 = a n 2 a n + 1 a_{n+1}={a_n}^{2}-a_n+1 , we obtain 1 a n + 1 1 a n + 1 1 = 1 a n 1 1 a n \frac{1}{a_{n+1}} \leq \frac{1}{a_{n+1}-1}=\frac{1}{a_{n-1}}-\frac{1}{a_n} .

This gives 1 a 3 1 a 1 1 a 2 \frac{1}{a_3} \leq \frac{1}{a_1}-\frac{1}{a_2} , 1 a 4 1 a 2 1 a 3 \frac{1}{a_4} \leq \frac{1}{a_2}-\frac{1}{a_3} etc, so taking summations we get i = 1 n 1 a i 1 a 1 + 1 a 2 + 1 a 1 1 a n 1 = 29 13 1 a n 1 < 3 \sum_{i=1}^{n}\frac{1}{a_i} \leq \frac{1}{a_1}+\frac{1}{a_2}+\frac{1}{a_1}-\frac{1}{a_{n-1}}=\frac{29}{13}-\frac{1}{a_{n-1}} < 3 for n 3 n \geq 3 .

It is easy to observe that the a i {a_i} are always positive (in fact >1) from a n + 1 = a n ( a n 1 ) + 1 a_{n+1}=a_n(a_n-1)+1 . Therefore, i = 1 n 1 a i < 3 \lfloor\sum_{i=1}^{n}\frac{1}{a_i}\rfloor<3 and so can only take the values 0 , 1 , 2 {0,1,2} .

Finally, it is easy to observe that 1 a 1 = 0 \lfloor\frac{1}{a_1}\rfloor=0 , 1 a 1 + 1 a 2 = 1 \lfloor\frac{1}{a_1}+\frac{1}{a_2}\rfloor=1 and 1 a 1 + 1 a 2 + 1 a 3 = 2 \lfloor\frac{1}{a_1}+\frac{1}{a_2}+\frac{1}{a_3}\rfloor=2 , hence the answer.

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...